PERSEPSI KELOMPOK TANI TERHADAP PROGRAM PEMBERDAYAAN MASYARAKAT â€œBUDIDAYA LEBAH MADU Apismelliferaâ€ DI TAHURA Ir. H. DJUANDA BANDUNG - Ramdani, Fahrizal; Panjaitan, Poltak BP; Meiganati, Kustin Bintani (Jurnal Nusa Sylva, 2014)
One work program of the Central Management Forest ParkIr. H.Juandain 2013 is the empowerment of communities through activities Apismellifera bee keeping and mushroom cultivation tim berintended forrural communities around Forest ParkIr. H.Juandathe Village Langensari and Ciburial. The purpose of this researchis to find out the perceptions and attitudes offarmers' groups towards community empowerment programs around Forest Park. The results of the study explained that the perception of farmers' group is to agree with the holding of beekeeping program, where they already understand the importance of beekeeping for environmental conservation and increase their income. However, for the attitude of farmers' groups in the running in the category of low because farmers are not motivated to do beekeeping. due to limited feed, difficulties in the herd of bees, funding, technical assistance and efforts to address the threat.